2015
DOI: 10.1021/acs.organomet.5b00607
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-Catalyzed Amine–Silane Dehydrocoupling: Extended Reaction Scope with a Phosphorus-Based Ligand

Abstract: The scope of the catalytic dehydrocoupling of primary and secondary amines with phenylsilanes has been investigated using [Y{N-(SiMe 3 ) 2 } 3 ] and a four-coordinate analogue bearing a cyclometalated phosphonium methylide ligand. Inclusion of the phosphorus-based ligand on yttrium results in increased substrate scope in comparison to the tris(amide) analogue. While reversible C−H bond activation of the cyclometalated ligand was observed in stoichiometric experiments, Dlabeling experiments and DFT calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…[10] Elsewhere,w ea nd others have shown that oxophilic,d 0 metal complexes provide competent precatalysts to dehydrocouple hydrosilanes and amines. [11][12][13][14] Barium compounds in particular catalyze the coupling of diamines and di(hydrosilanes). [14a,b] We present here an extension of this work to the barium-mediated production of polycarbosilazanes.T he rapid and controlled syntheses of either linear or cyclic polymers by dehydropolymerization of p-xylylenediamine (represented as H 2 N^^NH 2 )a nd diphenylsilane, together with detailed characterizations,a re reported (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Elsewhere,w ea nd others have shown that oxophilic,d 0 metal complexes provide competent precatalysts to dehydrocouple hydrosilanes and amines. [11][12][13][14] Barium compounds in particular catalyze the coupling of diamines and di(hydrosilanes). [14a,b] We present here an extension of this work to the barium-mediated production of polycarbosilazanes.T he rapid and controlled syntheses of either linear or cyclic polymers by dehydropolymerization of p-xylylenediamine (represented as H 2 N^^NH 2 )a nd diphenylsilane, together with detailed characterizations,a re reported (Scheme 1).…”
mentioning
confidence: 99%
“…With 10 % excess,t he polymer P6,w ith am olecular weight of about 4500 gmol À1 ,c orresponding to X n,exp = 28, was obtained (entry 6). [21] Them ain resonances in the 1 H( d = 4.09 and 1.42 ppm), 13 C{ 1 H} (d = 45.79 ppm), and 29 Si{ 1 H} (d = À24.32 ppm) NMR spectra of P5-P7 match those for P2 and P3,t hus confirming the preponderance of regular repetitive units in the polymer backbone ( Figure 4). Thep olycarbosilazane P7,w hich is of comparatively high molecular weight (ca.…”
mentioning
confidence: 99%
“…Limited by a small substrate scope, only nonsterically hindered amines and silanes can be utilized. Subsequently, the Crimmin group has reported dehydrocoupling by incorporating yttrium(III) disilazide and its analogues in the form of a four‐coordinated species bearing a cyclometalated phosphonium methylide ligand . The ligand's presence results in better catalytic activity than that observed for the simple disilazide.…”
Section: Silicon–nitrogen Bond Formationmentioning
confidence: 99%
“…As a result, significant efforts have been devoted to provide an alternative protocol to create Si−N bonds using N−H/H−Si CDC reactions. Catalyzed reactions have largely involved catalysts based on Ti IV , Al III , Cu I , Rh I ,, Ru 0 , Yb II ,, Y III , Zn II , and U IV , or also metal‐free frustrated Lewis pairs (FLPs) ,. Si−N coupling catalyzed by main‐group metal reagents, chiefly group 2, is particularly effective.…”
Section: Introductionmentioning
confidence: 99%